The Comparative Evaluation Of Outcomes Of Asthma Treatment Through Use Of Regimen That Contain Fluticasone Versus Other Types Of Treatment Regimen In Private And Public Hospitals In Erbil, Iraq - Maulood, Karwan Bahram (2023)
Erbil is one of the cities in Iraq that was heavily involved in war during the Iraq-USA conflicts. Due to the chemicals and weapons used in this war, millions of people now suffer from asthma. Another major contributor to asthma cases in this province is the dust storms that blow in a lot of dust pollution. War caused a total breakdown in supply chains and healthcare systems, making it difficult to get treatment and lowering people's quality of life overall. The goal of this study was to measure the quality of life (QOL) and knowledge, attitudes, and practices (KAP) of asthmatic patients with bronchial asthma and come up with a better treatment plan using inhaled corticosteroid (ICS) and health education. This study is designed in two phases. In the first phase, a quasi-experimental study was carried out to assess the QOL and clinical outcomes following treatment with three different ICS (Fluticasone, Budesonide, and Beclomethasone). For objectives 1 and 2, 105 and 250 patients for objective 3 were recruited, respectively. The Mini Asthma Quality of Life Questionnaire (mini-AQLQ) was used to assess the QOL. The clinical outcomes following ICH treatments include forced expiratory volume in 1 second (FEV1) from spirometry, eosinophil count and Vitamin D assay from serum blood. Both QOL and ICS data were collected at baseline, 2 week, and 12-week intervals. In phase II, 250 patients were recruited for KAP assessment.